2018
DOI: 10.1891/0886-6708.vv-d-17-00136
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle-Routine Activities, Neighborhood Context, and Ethnic Hate Crime Victimization

Abstract: There is little empirical work examining how individuals’ characteristics and lifestyles may influence hate crime victimization. In addition, while recent research suggests that social disorganization theory is useful for understanding hate crime, more studies are needed to understand how community characteristics influence hate crime victimization. This study conducts multilevel models using survey data from approximately 3,700 individuals nested within 123 neighborhoods in order to examine whether lifestyles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…In other words, essential workers are more frequently in public settings in which they are able to be targeted, while those who engage in total social distancing are more likely to be at home. These findings are consistent with prior research on routine activities, lifestyle factors and non-pandemic related victimization (see McNeeley & Overstreet, 2018)-as well as research on non-Asian hate crime during the pandemic (see Wenger & Lantz,202 a,202 b)-which finds that those individuals with more exposure to potential hate crime offenders (i.e., essential workers who could not "stay at home") are more likely to be the victims of hate crime. Finally, those who became unemployed during the pandemic are more likely to have been victimized than those who were already unemployed prior to the pandemic.…”
Section: Np1105supporting
confidence: 92%
“…In other words, essential workers are more frequently in public settings in which they are able to be targeted, while those who engage in total social distancing are more likely to be at home. These findings are consistent with prior research on routine activities, lifestyle factors and non-pandemic related victimization (see McNeeley & Overstreet, 2018)-as well as research on non-Asian hate crime during the pandemic (see Wenger & Lantz,202 a,202 b)-which finds that those individuals with more exposure to potential hate crime offenders (i.e., essential workers who could not "stay at home") are more likely to be the victims of hate crime. Finally, those who became unemployed during the pandemic are more likely to have been victimized than those who were already unemployed prior to the pandemic.…”
Section: Np1105supporting
confidence: 92%
“…The relationship also breaks down in more advantaged neighborhoods, where people may not be as willing to admit that such things happen in their neighborhood. Another study of neighborhood contexts found that neighborhoods that were low in collective self-efficacy were more likely to experience bias crimes (McNeeley & Overstreet, 2018). Causality is difficult to discern in these neighborhood-based studies, but given the research to date discussed in this chapter, the community impacts of bias crime-creating boundaries between people, making them suspicious of one another, breaking down their neighborliness, and decreasing their collective sense of being one community-most likely invites more bias crimes.…”
Section: Community At-large: Harms To Community Dynamicsmentioning
confidence: 95%
“…This contingency is writ large for Muslim women. When she is in a predominantly Muslim neighbourhood – a context where she is just like our sisters and mothers – she is an ideal, deserving subject and guardians appear from all directions; bystanders, authorities, and business owners (McNeeley and Overstreet, 2018). However, when she is culturally isolated – going about her routine activities in a neighbourhood where she is the visible minority – she is a flawed, undeserving, (un)victim (Long, 2021).…”
Section: Islamophobia Gender and Routine Victimisationmentioning
confidence: 99%